A Way to Supress Chaos in the Cubic-Quintic Duffing Van der Pol Equation - Salas S., Alvaro H. (Research and Applications Towards Mathematics and Computer Science Vol. 9, 2024)
In this paper we apply several techniques to achieve analytic approximate and numerical solutions of the cubic–quintic Duffing–van der Pol equation. This equation represents a second-order ordinary differential equation with quintic nonlinearity and includes two external periodic forcing terms. We permorm Melnikov analysis in order to detect chaotic beahvior.